Mercury may reduce the protective effect of sea fish consumption on serum triglycerides levels in Chinese adults: Evidence from China National Human Biomonitoring. (15th October 2022) - Wu, Bing; Qu, Yingli; Lu, Yifu; Ji, Saisai; Ding, Liang; Li, Zheng; Zhang, Miao; Gu, Heng; Sun, Qi; Ying, Bo; Zhao, Feng; Zheng, Xulin; et al.
Abstract: Sea fish contain omega-3 polyunsaturated fatty acids (omega-3 PUFAs) which have been found to reduce triglyceride (TG) levels. However, sea fish may contain pollutants such as mercury which cause oxidative stress and increase TG levels. Therefore, the relationship between sea fish and TG remains unclear. We aimed to explore whether blood mercury (BHg) can affect the effect of sea fish consumption frequency on TG level among Chinese adults. A total of 10, 780 participants were included in this study. BHg levels were measured using inductively coupled plasma mass spectrometry (ICP-MS). The associations of sea fish consumption frequency with BHg and TG levels as well as the association of BHg with TG levels were evaluated using multiple linear regression. Causal mediation analysis was used to evaluate the mediation effect of BHg levels on the association of sea fish consumption frequency with TG levels. The frequency of sea fish consumption showed a negative association with TG level. Compared with the participants who never ate sea fish, the TG level decreased by 0.193 mmol/L in those who ate sea fish once a week or more [β (95%CI): −0.193 (−0.370, −0.015)]. Significant positive associations were observed of BHg with TG levels. With one unit increase of log2-transformed BHg, the change of TG level was 0.030 mmol/L [0.030 (0.009, 0.051)]. The association between sea fish consumption and TG was mediated by log2-transformed BHg [total effect = −0.037 (−0.074, −0.001); indirect effect = 0.009 (0.004, 0.015)], and the proportion mediated by log2-transformed BHg was 24.25%. BHg may reduce the beneficial effect of sea fish consumption frequency on TG levels among Chinese adults. Overall, sea fish consumption has more benefits than harms to TG. Graphical abstract: Mercury may reduce the protective effect of sea fish consumption frequency on triglycerides. Image 1 Highlights: Sea fish consumption was negatively associated with TG and positively associated with BHg. BHg was positively associated with TG levels. BHg acts as a mediator in the relationship of sea fish consumption frequency with TG. BHg may reduce the protective effect of sea fish consumption on serum TG levels.